Implications of the Work From Anywhere Policy from the Perspective of Employment Law and Public Service: A Case Study of the Central Bengkulu Regency Government - Muhammad Yogi Nofran; M. Azzah Rozanda; Fadel Jovinka; Iskandar Iskandar; Madinar Madinar (The Future of Education Journal, 2026)
The Work From Anywhere (WFA) policy established through the Circular Letter of the Regent of Bengkulu Tengah Number 000.8.3/0014/B.7/1/2026 introduces a flexible working arrangement for civil servants (ASN) within the Bengkulu Tengah Regency Government, stipulating that civil servants are required to work from office for three days per week while being permitted to work from any location for the remaining two days. This study examines two principal legal issues: first, the conformity of the WFA policy with the hierarchy of civil service regulations in Indonesia, and second, its implications for the fulfilment of public service obligations toward the community from the perspective of excellent public service principles. The research employs a normative legal method with statute and case study approaches. The findings indicate that although the Regent possesses attributed authority to establish internal personnel policies, the Circular Letter does not occupy a formal position within the statutory hierarchy, thus limiting its binding force to the internal scope of the agency. Furthermore, the three-day office work scheme carries a risk of reduced public service accessibility and responsiveness if not accompanied by adequate service substitution mechanisms. The study recommends strengthening the legal foundation through a Regent Regulation and establishing an integrated quality assurance system for public services during WFA implementation.